RESPON PENONTON TERHADAP KONTESTASI PILPRES: Respon Penonton Terhadap Kontestasi Pilpres - Sabiruddin Sabiruddin (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2021)
The beginning of the debate over media content in Indonesia surfaced during the 2014 Presidential and Vice Presidential election contestation. The first volume of Jokowi and Prabowo's fight in the 2014 Presidential and Vice-Presidential Election turned into a free stage for Metrotv with the Prime Time program and Tvone's Kabar Evening program as meaning producers. This study problematic both questions by placing the audience as a determinant of the authority of meaning. Methodologically, this research is a study of the audience using an interpretive approach using the Decoding Encoding Theory introduced by Stuart Hall as an analytical tool. Researchers selected four student informants who have different social and scientific backgrounds. The results of this study show that the audience's encoding is in a dominant hegemonic position seen in Rizki Pratama, Julia Mandani and Sitti Rohmani. Meanwhile, Muhammad Miftahul Mubarok with an activist background is in a resistant position.